Using Whole Genome Sequencing in an African Subphenotype of Myasthenia Gravis to Generate a Pathogenetic Hypothesis - Nel, Melissa; Mulder, Nicola; Europa, Tarin A.; Heckmann, Jeannine M. (Frontiers in Genetics, 2019)
Myasthenia gravis (MG) is a rare, treatable antibody-mediated disease which is characterised by muscle weakness. The pathogenic antibodies are most frequently directed at the acetylcholine receptors (AChRs) at the skeletal muscle endplate. An ophthalmoplegic subphenotype of MG (OP-MG), which is characterised by treatment resistant weakness of the extraocular muscles (EOMs), occurs in a proportion of myasthenics with juvenile symptom onset and African genetic ancestry. Since the pathogenetic mechanism(s) underlying OP-MG is unknown, the aim of this study was to use a hypothesis-generating genome-wide analysis to identify candidate OP-MG susceptibility genes and pathways. Whole genome sequencing (WGS) was performed on 25 AChR-antibody positive myasthenic individuals of African genetic ancestry sampled from the phenotypic extremes: 15 with OP-MG and 10 individuals with control MG (EOM treatment-responsive). Variants were called according to the Genome Analysis Toolkit (GATK) best practice guidelines using the hg38 reference genome. In addition to single variant association analysis, variants were mapped to genes (+/- 200kb) using VEGAS2 to calculate gene-based test statistics and HLA allele group assignment was inferred through “best-match” alignment of reads against the IMGT/HLA database. While there were no single variant associations that reached genome-wide significance in this exploratory sample, several genes with significant gene-based test statistics and known to be expressed in skeletal muscle had biological functions which converge on muscle atrophy signalling and myosin II function. The closely linked HLA-DPA1 and HLA-DPB1 genes were associated with OP-MG subjects (gene-based p<0.05) and the frequency of a functional A>G SNP (rs9277534) in the HLA-DPB1 3’UTR, which increases HLA-DPB1 expression, differed between the two groups (G-allele 0.30 in OP-MG vs 0.60 in control MG; p=0.04). Furthermore, we show that rs9277534 is an HLA-DBP1 expression quantitative trait locus in patient-derived myocytes (p<1x10-3). The application of a SNP to gene to pathway approach to this exploratory WGS dataset of African myasthenic individuals, and comparing dichotomous subphenotypes, resulted in the identification of candidate genes and pathways that may contribute to OP-MG susceptibility. Overall, the hypotheses generated by this work remain to be verified by interrogating candidate gene and pathway expression in patient-derived extraocular muscle.